(untitled) (International Journal of Scientific Trends, 2026)
This article examines the work in the field of crime prevention among the youth of Uzbekistan. Analyzing the legislation and studying statistical data on the growth of crime in the youth environment, the author formulates recommendations and proposals for the prevention of antisocial behavior among young people. The rapid development of digital technologies has significantly transformed the lives of young people. Social media platforms, online gaming, instant messaging, and digital communities have become central to communication, education, and entertainment. While the digital space offers enormous opportunities for learning and self-expression, it also presents serious risks, including various forms of delinquency and cybercrime. Understanding these threats and developing effective prevention strategies is essential for protecting youth in the modern digital environment. In Uzbekistan, society is at a modern stage of development, and a person, his dignity, rights and freedoms are recognized as the highest values. The priority of human rights necessitates the establishment of benevolent relations between citizens while observing the rules of life in society, caring behavior in the upbringing of the younger generation, and the creation of conditions ensuring public health. This, in turn, requires citizens to comply with the rules of conduct and safety in society and with rules aimed at protecting public health.